The investigation of toxicokinetics parameters of cyanide and thiocyanate in mice - Sadettin Tanyıldızı; İbrahim Pirinçci; Sezai Kaya; Bünyamin Traş; Ender Yersan (Eurasian Journal of Veterinary Sciences)
The purpose of this study was to determine the some toxicokinetic parameters of cyanide and thiocyanate in mice experimentally poisoned with sodium cyanide. In the study, 200 mice, 40-50 g weights, were used. Sodium cyanide were given intraperitoneally in doses of 0,1, 0.2, 0.4 and 0.8 mg/kg. Then, some toxicokinetic parameters of the cyanide and thiocyanate like as distribution half-life, elimination half-life, mean existence lime and area under the curve (AUC) in the blood samples drawn at 6, 12, 30, 60, 120, 240, 360 ve 720th minutes were determined. The distribution half-lifes ol blood cyanide levels were, respectively, 0.04±0.02, 0.05±0.009. 0.06±0.008 and 0.08±0.01th hour; the elimination half-lifes were, respectively, 3.06±0.14, 2.36±0.02, 2.33±0.03 and 2.28±0.06 hours; the duration of maximal concentration was 12 minutes and the maximal blood levels, according to doses, respectively, were 0.153, 0.308, 0.350 and 0.376 µ,g/ml. Besides. mean existence times were, respectively, 4.53±0.20, 3.50±0.03, 3.46±0.05 and 3.43±0.12 hours and AUC values according to doses were, respectively, 33.50±2.62, 45.40±1.84, 48.91±2.77 and 58.47±2.54 µg.hour/ml were observed. The distribution half-lifes of blood thiocyanate levels were, respectively, 0.07±0.008, 0.09±0.005, 0.09±0.005 and 0.18±0.05 hours; the elimination hall-lifes were, respectively, 62.80±19.36, 25.79±2.65, 14.48±0.41 and 14.53±0.80 hours; the duration of maximal concentration 120 minutes and the maximal blood levels according to doses were, respectively, 0.265, 0246, 0.408 and 0.444 µg/ml. Besides, mean existence times were, respectively, 90.27±27.95, 37.37±3.83, 21.04±0.59 and 21.27±1.17 hours and AUC values according to doses were, respectively, 79.13±54.19, 28.06±15.38, 8.92±0.45 and 89.22±49.91 µg.hour/ml.